Current and emerging therapies to combat persistent intracellular pathogens. (October 2019) - Arandjelovic, Philip; Doerflinger, Marcel; Pellegrini, Marc
Highlights: Current antimicrobial therapies fail to eradicate persistent intracellular infections. Host-directed therapies (HDT) target host cell pathways to promote clearance of disease. Novel HDTs show promise in pre-clinical models and clinical trials. A combinatorial approach of HDTs with antimicrobial agents is most likely to succeed. Abstract : Intracellular pathogens such as HIV, hepatitis B virus, and Mycobacterium tuberculosis are responsible for millions of deaths worldwide and represent major obstacles to global health. Current treatment options have improved patient outcomes and extended life-expectancy in many countries; however, challenges such as latency, drug-resistance, and inflammatory pathology have necessitated advancements in curative strategies which go beyond the traditional antimicrobial focus. This review highlights recent advances in host-directed therapies to eradicate intracellular pathogens or augment the endogenous immune response by targeting host cell pathways. The 'kick and kill' strategy for HIV latency, adjunct immunomodulatory compounds for tuberculosis, and pro-apoptotic small-molecule inhibitors in the case of chronic Hepatitis B are promising examples of host-directed therapies that signal a paradigm shift in treatment and management of chronic infectious disease.